2008
DOI: 10.1007/s10067-007-0800-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cyclic citrullinated peptide-2 (CCP2) autoantibodies and extra-articular manifestations in Greek patients with rheumatoid arthritis

Abstract: The objective of our study was to establish whether there is an association between rheumatoid arthritis with extra-articular manifestations (exRA) and anti-cyclic citrullinated peptide 2 (anti-CCP2) antibodies in Greeks. A retrospective study of 220 Greek patients with RA, 95 with exRA and 125 without extra-articular manifestations (cRA). Serum anti-CCP2 antibodies and IgM rheumatoid factor (RF) were measured. CCP2(+) were 65.3% of exRA and 58.4% of cRA patients. RF(+) were 69.5% of exRA and 60.0% of cRA pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
3
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 17 publications
4
47
3
4
Order By: Relevance
“…Two main ACPAs are recognised, anti-cyclic citrullinated peptide (anti-CCP) and anti-mutated citrullinated vimentin (anti-MCV) antibodies. Both are markers of disease severity in rheumatoid arthritis [15,16] and there is some suggestion that they occur more in extra-articular disease [17], particularly lung disease [18]. We reasoned that pulmonary citrullination might be a relevant process generating autoantibodies in COPD, alongside elastin liberation.…”
mentioning
confidence: 99%
“…Two main ACPAs are recognised, anti-cyclic citrullinated peptide (anti-CCP) and anti-mutated citrullinated vimentin (anti-MCV) antibodies. Both are markers of disease severity in rheumatoid arthritis [15,16] and there is some suggestion that they occur more in extra-articular disease [17], particularly lung disease [18]. We reasoned that pulmonary citrullination might be a relevant process generating autoantibodies in COPD, alongside elastin liberation.…”
mentioning
confidence: 99%
“…15,38 The association of RF and extraarticular disease in RA is well known -the RF is considered a predictor of ExRA. The infl uence of each isotype in that association has been the object of recent studies.…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, Turesson et al 5 reported that anti-CCP was positive in 77% of the patients with ExRAs, while a Greek study has reported 65.3% of that association. 38 The presence of anti-CCP in patients with RA indicates more severe joint disease. The presence of citrullinated proteins in infl amed synovia suggests that they play an important role in the pathogenesis of RA.…”
Section: Discussionmentioning
confidence: 99%
“…. Связь между риском развития ИПЛ-РА и высо-ким уровнем РФ была подтверждена и в других исследова-ниях [37,55]. Данные о влиянии АЦЦП на развитие ИПЛ являются противоречивыми [56][57][58].…”
Section: ги с т о л о г и ч е с к а я и к л и н и ч е с к а я к л а сunclassified